2016
DOI: 10.1016/j.vetmic.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated porcine reproductive and respiratory syndrome virus vaccine adjuvanted with Montanide™ Gel 01 ST elicits virus-specific cross-protective inter-genotypic response in piglets

Abstract: The efficacy of a novel BEI-inactivated porcine reproductive and respiratory syndrome virus (PRRSV) candidate vaccine in pigs, developed at RIBSP Republic of Kazakhstan and delivered with an adjuvant Montanide™ Gel 01 ST (D/KV/ADJ) was compared with a commercial killed PRRSV vaccine (NVDC-JXA1, C/KV/ADJ) used widely in swine herds of the Republic of Kazakhstan. Clinical parameters (body temperature and respiratory disease scores), virological and immunological profiles [ELISA and virus neutralizing (VN) antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Evidently, this assertion may not always be true as the nature and mechanisms of action of adjuvants are highly diverse [27]. More recently, several groups have demonstrated that specific adjuvants can result in a large improvement in virus-based vaccines against PRRSV [32, 36, 37]. In our study, the causes behind the similarities between CMI responses against different strains and the boosts detected are unknown, as well as the early stimulation of NAs, and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, this assertion may not always be true as the nature and mechanisms of action of adjuvants are highly diverse [27]. More recently, several groups have demonstrated that specific adjuvants can result in a large improvement in virus-based vaccines against PRRSV [32, 36, 37]. In our study, the causes behind the similarities between CMI responses against different strains and the boosts detected are unknown, as well as the early stimulation of NAs, and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of influenza A virus and PRRSV-1 (EU) and -2 (US) was based on commercially available PCR diagnostic kits. A differentiation of PRRSV-1 and -2 was possible with the used PRRSV RT-PCR (EZ-PRRSVTM MPX 4.0 assay, Tetracore R, Rockville, MD, USA) [ 54 ]. All known swine influenza subtypes were detected with a commercially available RT-PCR (EZ-Universal Flu A 2.0 RT-PCR, Tetracore R, Rockville, MD, USA) [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different adjuvants (cytokines, chemical reagents, and bacterial products; detailed in Charerntantanakul, 2009 ), different administration routes (intramuscular or into the skin using dissolving microneedle patches), and different inactivation manners [binary ethyleneimine (BEI)-inactivated, beta-propiolactone (BPL)-inactivated, or ultraviolet (UV)-inactivated] have been tested to obtain inactivated PRRSV vaccine candidates to provide a better protective efficacy against clinical PRRSV isolate infection in piglets. Although some attempts could induce humoral immune responses, no successful cases have been reported that provided satisfactory protection efficacy to relieve clinical symptoms and reduce viremia and the pathological changes in the lung and other organs ( Nilubol et al, 2004 ; Tabynov et al, 2016 ; Vreman et al, 2019 , 2021 ).…”
Section: Molecular Characterization (Genetic Diversity Of Viruses)mentioning
confidence: 99%